Studies on the adsorption and corrosion inhibition of substituted benzylidene Schiff bases on mild steel in 1 M HCl / Nor Zakiah Nor Hashim - Nor Hashim, Nor Zakiah (Institute of Graduate Studies, UiTM, 2016)
The objective of this thesis is to investigate the performance of newly synthesized substituted benzylidene Schiff bases as corrosion inhibitors of mild steel in 1 M HCl at 25°C. To accomplish this intention, a series of (E)-N’-benzylidene-N⁴-phenylbenzene-1,4-diamine Schiff bases that contain different substituent groups at para position of benzylidene were synthesized and characterized via physical and spectroscopic analysis. The azomethine double bond (C=N) infrared spectra found for the Schiff bases are at around 1590-1604 cm⁻¹. From ¹H Nuclear Magnetic Spectroscopy (NMR) spectra, the azomethine proton (singlet) shifted in the range of δ 8.634-8.531 ppm, while the peaks at around δ 157.32-155.82 ppm found in ¹³C NMR spectra are assigned for azomethine carbon. The corrosion inhibition performance of N-phenyl-1,4-phenylenediamine (NPPD), (E)-N¹-benzylidene-N⁴-phenylbenzene-1,4-diamine (K1), N-[(E)-4- chlorobenzylidene]-N’-phenylbenzene-1,4-diamine (K2) and N-[(E)-4- methoxybenzylidene]-N’-phenylbenzene-1,4-diamine (K3) was measured in 1 M HCl using electrochemical methods which are polarization, Linear Polarization (LPR) and Electrochemical Impedance Spectroscopy (EIS). The analysis of substrate’s surface via Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM) and X-ray Photoelectron Spectroscopy (XPS) was employed to determine the Schiff base adsorption behaviour on the surface of mild steel in the acidic solution. The electrochemical results revealed that the corrosion inhibition efficiencies of the Schiff bases are higher and achieved up to 96.0% as found for K2, thus more effective than the other Schiff base in the series, and the parent amine of NPPD. The adsorption of inhibitors at the metal-solution interface are well described based on Langmuir adsorption isotherm because R² and slope values are almost to the value of 1…